Delayed deterioration following the evacuation of posterior fossa extradural hematoma - Amit Agrawal (Romanian Neurosurgery, 2015)
A missed or delayed detection of intracranial injuries can lead to progressive neuronal damage and secondary brain damage. We present a case of 45 year female presented 8 after the road traffic accident and had a large posterior extradural hematoma on left side with mass effect. In addition there was a small speck of right frontal contusion with localized cerebral edema. The patient initially improved after evacuation of the hematoma. However on 3rd post-operative day she was complaining of headache and became progressively drowsy. A follow up CT scan showed increase in peri-lesional edema around the right frontal contusion with squashing of the lateral ventricles suggestive of diffuse cerebral edema. The patient was shifted back to intensive care unit and responded well to further conservative management. In our patient the events could be collaborated well with existing evidence (presence of contrecoup contusion and on clinical deterioration at day 3).